PTU-064 Trends in Mortality for IBD Patients Admitted as an Emergency to English Hospitals: A 10-Year Analysis of Routine Administrative Data. (17th August 2016) - Shawihdi, M; Driscoll, R; Pearson, M; Cummings, F; Bloom, S; Williamson, P; Bodger, K
Abstract : Introduction: To support the development of metrics for the UK IBD Registry, techniques are being developed to analyse Hospital Episode Statistics (HES) for England. This report is focused on in-hospital deaths (In-HD) recorded for all-cause and cause-specific emergency admissions (Em-Ad) among a nationwide cohort of IBD patients over ten years. Consecutive rounds of UK IBD Audit have suggested declining inpatient mortality in the UK, albeit limited by incomplete case capture and ascertainment bias. Methods: COHORT: Any patient with a coded diagnosis of ulcerative colitis or Crohn's disease, identified between 04/05 to 13/14. DATA EXTRACT: All-cause hospital episodes belonging to the cohort during this period (Source: Health & Social Care Information Centre). ANALYSIS: Datasets were interrogated using algorithms in IBM-SPSS, SAS and Excel, with admission and patient-level analyses. We applied a range of definitions to extract IBD-associated Em-Ad based on coded diagnoses and procedures, ranging from a narrow focus (primary diagnosis of IBD-specific codes) to broader categories (flagging of specific GI symptoms [R-codes] or selected conditions, complications or procedures suggestive of an IBD-related Em-Ad). Coding lists were informed by steering group review. Numbers and crude population-based rates of Em-Ad and In-HD were examined for each category of Em-Ad. Risk-adjusted odds ratio of death (OR) for each year were compared (co-variates: age, gender, Charlson index, Cancer codes), relative to baseline (04/05), in logistic regression models at individual patient level (first admission). Mid-year populations for England (18+) were obtained from ONS. Results: 352, 614 IBD patients had 887, 837 all-cause Em-Ad (aged 18+). Focusing only on admissions with a primary diagnosis of IBD, there were 141, 063 Em-Ad (UC = 60, 278; CD = 80, 785); 1, 701 in-hospital deaths; a year-on-year decline in crude admission death rate (2.0% to 0.7%) and population-based rate (0.60 to 0.28 I-HD per 100, 000 population). Relative to baseline year, the risk-adjusted odds ratio (OR) for death during Em-Ad (first admission with primary diagnosis; n = 82, 248 patients) declined steadily over the decade (2013/14 vs 2004/5, OR: 0.43 [0.33 to 0.56]). Further modelling and sensitivity analyses will be reported. Conclusion: Over the last decade there has been a significant reduction in hospital mortality for IBD patients admitted as an emergency to English hospitals. Although many factors may contribute to these improved statistics, the time period included 4 rounds of UK wide audit focusing on raising standards for in-patient care. Disclosure of Interest: M. Shawihdi Grant/research support from: Crohn's & Coliitis UK, R. Driscoll Consultant for: AbbVie, M. Pearson: None Declared, F. Cummings: None Declared, S. Bloom: None Declared, P. Williamson: None Declared, K. Bodger Grant/research support from: Crohn's & Colitis UK, Speaker bureau with: AbbVie